2006
DOI: 10.1681/asn.2005121334
|View full text |Cite
|
Sign up to set email alerts
|

Fewer Mega-Trials and More Clinically Oriented Studies in Hypertension Research? The Case of Blocking the Renin-Angiotensin-Aldosterone System

Abstract: In recent years, medical practice has been influenced substantially by several factors, including the overwhelming development of evidence-based medicine, which is a consequence of the impressive, growing number of large clinical trials, the so-called "mega-trials." These clinical studies are designed mostly to investigate the effects of drugs or treatments on hard end points that cannot be tested by individual physicians in their daily clinical practice. The growing role of this epidemiologic approach to medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…10,11 Results of large, randomized, controlled clinical trials demonstrated that it is possible to reach these BP targets in large proportions of treated patients with hypertension having different cardiovascular risk profiles. [12][13][14] Indeed, the design of these clinical trials systematically included antihypertensive therapies based on drugs inhibiting the renin-angiotensin system (RAS) and calcium channel blockers (CCBs) compared to b-blockers and diuretics. [12][13][14] On the basis of these findings, a preferred use of these antihypertensive drug classes have been pursued by recent hypertension guidelines, in order to bridge the gap between the attained and expected BP control rates, to ensure adequate adherence and persistence to prescribed medications and to improve cardiovascular outcomes in treated patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Results of large, randomized, controlled clinical trials demonstrated that it is possible to reach these BP targets in large proportions of treated patients with hypertension having different cardiovascular risk profiles. [12][13][14] Indeed, the design of these clinical trials systematically included antihypertensive therapies based on drugs inhibiting the renin-angiotensin system (RAS) and calcium channel blockers (CCBs) compared to b-blockers and diuretics. [12][13][14] On the basis of these findings, a preferred use of these antihypertensive drug classes have been pursued by recent hypertension guidelines, in order to bridge the gap between the attained and expected BP control rates, to ensure adequate adherence and persistence to prescribed medications and to improve cardiovascular outcomes in treated patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Indeed, the design of these clinical trials systematically included antihypertensive therapies based on drugs inhibiting the renin-angiotensin system (RAS) and calcium channel blockers (CCBs) compared to b-blockers and diuretics. [12][13][14] On the basis of these findings, a preferred use of these antihypertensive drug classes have been pursued by recent hypertension guidelines, in order to bridge the gap between the attained and expected BP control rates, to ensure adequate adherence and persistence to prescribed medications and to improve cardiovascular outcomes in treated patients with hypertension. 10,11 Being the vast majority of these evidence based on the use of dihydropyridinic CCBs, these drugs are now recommended both as first-line therapy and as an ideal partner for dual or triple combination therapies for the clinical management of hypertension and hypertension-related comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] As such, ECG detection, as well as regression of cardiac OD, namely LVH, can be viewed as an intermediate endpoint that may help physicians during the long-term clinical management of hypertension. 33,34 Over the past years, several novel ECG criteria for LVH have been tested for the diagnostic workup of hypertensive outpatients in order to try to overcome some intrinsic limitations of this approach and to ameliorate its relatively low specificity. 35 The applicability of these new diagnostic criteria, however, was at least, in part, limited to frankly hypertensive populations (ie, patients with established diagnosis of hypertension under pharmacologic treatment), and it has not been tested in untreated, recently diagnosed hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…The benefi ts of RAS-inhibiting drugs in different clinical conditions have been demonstrated in different clinical settings, from asymptomatic patients with cardiac disease to severe refractory heart failure, end-stage renal disease and cardiovascular death [ 37 ]. In particular, the favourable effects of RAS-blocking agents, including both ACE inhibitors and ARBs, as compared to conventional treatment (mostly including beta-blockers and diuretics) have been extensively tested in a large, representative population and corroborated by the achievement of reduced cardiovascular morbidity and mortality [ 37 ].…”
Section: Rationale For Combination Therapies Based On Ras Antagonismmentioning
confidence: 99%
“…In particular, the favourable effects of RAS-blocking agents, including both ACE inhibitors and ARBs, as compared to conventional treatment (mostly including beta-blockers and diuretics) have been extensively tested in a large, representative population and corroborated by the achievement of reduced cardiovascular morbidity and mortality [ 37 ]. On the basis of the observation that in most cases both ACE inhibitors or ARBs were systematically associated with other classes of antihypertensive drugs, mostly thiazide diuretics or CCBs, it has been suggested that implementing the use of combination therapies based on drugs able to inhibit the deleterious effects of abnormal RAS activation may also improve BP control and tolerability, beyond the favourable effects on cardiovascular protection in the clinical management of hypertension.…”
Section: Rationale For Combination Therapies Based On Ras Antagonismmentioning
confidence: 99%